2006
DOI: 10.1287/opre.1060.0277
|View full text |Cite
|
Sign up to set email alerts
|

A Branch-and-Cut Algorithm Without Binary Variables for Nonconvex Piecewise Linear Optimization

Abstract: We give a branch-and-cut algorithm for solving linear programs (LPs) with continuous separable piecewise-linear cost functions (PLFs). Models for PLFs use continuous variables in special-ordered sets of type 2 (SOS2). Traditionally, SOS2 constraints are enforced by introducing auxiliary binary variables and other linear constraints on them. Alternatively, we can enforce SOS2 constraints by branching on them, thus dispensing with auxiliary binary variables. We explore this approach further by studying the inequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(52 citation statements)
references
References 13 publications
0
52
0
Order By: Relevance
“…The extension of lifting to the nonlinear or continuous setting is not new: see [17], [27], [34], and [7]. Also see [16], which lifts "tangent" inequalities to approximate multilinear functions.…”
Section: Motivation and Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…The extension of lifting to the nonlinear or continuous setting is not new: see [17], [27], [34], and [7]. Also see [16], which lifts "tangent" inequalities to approximate multilinear functions.…”
Section: Motivation and Backgroundmentioning
confidence: 99%
“…The construction that culminates in Definition 2.5 is a generalization of the classical lifting construction in mixed-integer programming (see [44], [27], [34], [7]). The LFO inequality at y uses the local structure of P to strengthen the linearization inequality (2); the strengthening is only local, however the LFO inequality is (globally) valid.…”
Section: Lifted First-order Cutsmentioning
confidence: 99%
“…Some recent work concerning piecewise linear functions that are not referenced in [155] include [151,51,57,124,62,123,126,127,43,156,153]. Finally, we note that there is also a vast literature on incorporating piecewise linear functions into optimization models without using MIP [17,54,55,56,38,99,158,47,169,46] Functions with bounded MIP representable graphs and epigraphs include most piecewise linear functions. In particular, for continuous multivariate functions with bounded domain we can give the following precise characterization.…”
Section: Mip Representability Of Functionsmentioning
confidence: 99%
“…They can be solved with algorithms such as the one proposed by Keha et al [89], a branch-and-cut algorithm without auxiliary binary variables for solving non-convex separable piecewise linear optimization problems that uses cuts and applies SOS2 branching. They can also be modeled as mixed integer programming (MIP) problems, following the work shown by Croxton et al [90], where it was demonstrated that the linear programming relaxation of three textbook mixedinteger programming models for non-convex piecewise linear minimization problems are equivalent, each approximating the cost function with its lower convex envelope.…”
Section: Piecewise Linear Functions and Non-convex Optimizationmentioning
confidence: 99%